First Photographic (Camera Trap) Evidence of Tibetan Wolf Canis lupus chanco in the Uttarakhand Himalaya, India - Maurya, Vipul; Meena, D. S.; Singh, Paramjit; Dhakate, Parag M.; Lal, S. B. (Journal of the Bombay Natural History Society (JBNHS), 2016)
No Abstract.